Etnomatemática para el aprendizaje de matemática de los estudiantes de educación general básica, de la Unidad educativa Nuestro Mundo Eco-Rio. - Guamán Cando, Jhonny Lenin (2020)
Research has demonstrated that including ethnomathematics in the classroom is an essential aspect that promotes innovation and improvement processes in educational institutions. However, not every process related to this type of knowledge improves substantially in teaching due to ignorance and lack of invention. For this reason, this research intends to propose forms of ethnomathematical thought from diverse sociocultural perspectives that strengthen the learning of mathematics in students of Basic Education. A mixed approach was established, with qualitative and quantitative techniques. It is a non-experimental study, purposeful and primary type considered bibliographic and field. Due to time, it was established as a cross-sectional study. Inductive and deductive methods were handled, with survey and interview techniques, instruments such as the questionnaire and an interview guide to collect the necessary information that was subsequently analyzed and interpreted. For greater consistency, the process of validity and reliability of instruments verified by three experts was carried out to carry out the triangulation of the information later. The research had a total population of 418 students and a non-probabilistic and intentional sample of 23 students from the 5th year of elementary school. Finally, it was concluded that the forms of ethnomathematical thought are of vital importance for strengthening mathematics, recommending both teachers and students to work with this type of activity elaborated by native peoples. Based on the problems and information collected on ethnomathematical aspects, a solution is established through the proposal of the Didactic Guide, elaborated with ethnomathematical thoughts and activities that strengthen the learning of mathematics.